2023
DOI: 10.2147/nss.s396853
|View full text |Cite
|
Sign up to set email alerts
|

The Accuracy and Reliability of Sleep Staging and Sleep Biomarkers in Patients with Isolated Rapid Eye Movement Sleep Behavior Disorder

Abstract: Purpose This study aimed to establish the diagnostic accuracy of a previously validated sleep staging system in patients with probable isolated REM sleep behavior disorder (iRBD), and to compare physicians’ diagnoses of iRBD based on REM sleep without atonia (RSWA) to non-REM hypertonia (NRH), a sleep measure independently associated with Parkinsonian spectrum disorders. Patients and Methods Twenty-six patients with a history of dream enactment behavior underwent a diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The extraction of sleep biomarkers from a frontal montage enabled self-application and in-home acquisition but deviated from conventional in-laboratory montages (16). Sleep staging is more difficult in patients with a NDD with any montage, however we previously demonstrated that auto-staging from a frontal montage combined with technical review was superior to visual staging of PSG recordings using the standard montage for detection of stages N3 and REM in iRBD patients (20). Importantly, the automated NRH and spindle duration algorithms required no technical review to achieve the reported detection accuracy and reliability.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The extraction of sleep biomarkers from a frontal montage enabled self-application and in-home acquisition but deviated from conventional in-laboratory montages (16). Sleep staging is more difficult in patients with a NDD with any montage, however we previously demonstrated that auto-staging from a frontal montage combined with technical review was superior to visual staging of PSG recordings using the standard montage for detection of stages N3 and REM in iRBD patients (20). Importantly, the automated NRH and spindle duration algorithms required no technical review to achieve the reported detection accuracy and reliability.…”
Section: Discussionmentioning
confidence: 97%
“…It appears that NRH may have utility in assessing advanced stages of synucleinopathies when REM sleep is limited, or detection impaired by delta and theta intrusion. Data are currently being acquired to further investigate the association between NRH and RSWA across a range of Parkinsonian spectrum disorders (20).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, multiple studies have harnessed the SP in investigating sleep-related disorders. For instance, a study [37] evaluated the accuracy of a sleep staging system in patients with isolated REM sleep behavior disorder (iRBD). This study compared physicians' diagnoses of iRBD based on REM sleep without atonia (RSWA) and non-REM hypertonia (NRH) using data collected from both SP and PSG recordings.…”
Section: The Sleep Profiler (Sp)mentioning
confidence: 99%